Acid demineralization effect on the sonication-assisted solvent extraction of vitrinite coal of the Powder River Basin. (15th January 2022) - Ogunsakin, Olakunle R.; Holberg, Stefan; Wang, Xinyan; Goroncy, Alexander; Adams, Jeramie; Johnson, Patrick
Highlights: Demineralization of subbituminous coal without destruction of the coal structure. The demineralization step boosted solvent extraction yields by factors of 1.9 to 4. Extraction yield increased with increasing solvent basicity and donor number. Extraction with ethylenediamine was 15% higher yield than pyridine or acetone. Abstract: Solvent-extraction of economic low-grade coals has gained recent interest as a way to produce new feedstocks for the synthesis of advanced carbon materials including polymers. Herein, we report the effect of coal demineralization by hydrochloric acid treatment on the sonication-assisted extraction of subbituminous coal from the Powder River Basin in Wyoming, USA at room temperature and the analysis of the initial and residual coals by FT-IR and solid-state 13 C NMR. The applied demineralization reduced ash content from 9.9% to 7% without any notable change in the coal composition or structure. Despite leaving the mineral matter in the coal, the demineralization significantly increased the extraction yield for all applied solvents, for ethylenediamine from 8.1% to 15.2%, for pyridine from 4.9% to 12.4%, and acetone from 1.1% to 4.5%.